Sierra Lammers: capstone - Lammers, Sierra, artist (Colorado State University. Libraries, 2025)
The artist's statement: Graphic design is my voice—an expression of my inner self. Through design, I can communicate what I often leave unsaid, using loud colors and emotive typography to boldly claim my voice. This body of work represents my approach to self-expression through graphic design. Each piece is a reflection of this, allowing me to articulate myself in ways that contrast my sometimes reserved first impression. Design often serves as a counterbalance to my introspection, creating a place for my true self to play, as well as the bold color and typography I often turn to. Ultimately, my work is an exploration of identity—a bridge between who I am and how I express it. Using evocative colors and emotive typography, I create visual narratives that are both personal and universal. I often turn to these elements to convey emotions or ideas that might be difficult to express through traditional means. The loud, vibrant colors in my work act as an extension of my personality—often more outspoken and extroverted than I tend to present. My modular typeface symbolizes this opportunity, as each character exists independently, yet can be rearranged and combined in endless ways. Each piece is a moment of self-reflection, offering insight into my personality, values, and inner conflicts. For me, design is not just an aesthetic pursuit—it's a deeply personal process. It is a journey of self-discovery through visual communication, where I challenge the boundaries of my own perception and invite others to engage with and interpret my personal narrative. Every time I engage with my work, it brings my inner world out, creating a space where my voice can be heard in a way that feels authentic and powerful.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design